Revisiting Perioperative Hair Removal Practices. (26th April 2019) - Edmiston, Charles E.; Leaper, David J.; Barnes, Sue; Johnson, Helen Boehm; Barnden, Marsha; Paulson, Marie H.; Wolfe, Jacob L.; Truitt, Karen
Abstract: The standard of practice for perioperative hair removal is largely based on research that is outdated and underpowered. Although there is evidence to support the practice of clipping instead of shaving, current recommendations are to remove hair only when absolutely necessary. Human hair is bacteria‐laden and challenging to disinfect, and clipping can be a safe method of hair removal that does not damage the skin. This article considers the removal of hair at the incision site with clippers, either before the patient enters the OR or in a manner that completely contains clipped hair, for every procedure, not just when absolutely necessary. There have been only two studies to date comparing clipping with no hair removal; more research is needed on this subject.